Analisis Pemulihan Spiritual dan Komunitas : Rekonstruksi Dasar Kehidupan dalam konteks Ezra 3:8-13 - Sona Simbolon; Elsa Herawati Lubis (Sukacita : Jurnal Pendidikan Iman Kristen, 2025)
This article delves deeply into the concept of Spiritual Restoration and Community: Rebuilding the Foundation of Life, with a focus on the text of Ezra 3:8-13. This research aims to gain a more comprehensive understanding of how the Israelites were interconnected in reaffirming the restoration of life through the reconstruction of the foundation of the Israelite nation. The research methods employed include biblical text analysis, historical studies, and an exposition of the cultural context of the time. The research findings provide a rich and complex perspective on the role of Ezra as a channel of God's will in restoring and guiding His people.